2013
DOI: 10.1108/20423891311294957
|View full text |Cite
|
Sign up to set email alerts
|

Educating the early career arts professional using a hybrid model of work based learning

Abstract: Purpose -Using data drawn from two cohorts of learners studying the Bachelor of Arts (Professional Practice) programme at Middlesex University, the purpose of this paper is to critically analyse the effectiveness of work based learning in improving the skills bases of early career arts professionals in the twenty-first century and to explore the changing place and role of "traditional" concepts of knowledge and teaching. Design/methodology/approach -This study utilised a collaborative action research approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Initially in 2009 Durrant and Akinleye redeveloped the first module for the undergraduate cohort of BAPP (Arts). Subsequent changes they made to the curriculum embraced the connectivity of social media (Middlesex University, 2009;Bryant et al, 2013). This new curriculum design aimed at acknowledging that work-based students were less physically present on campus but still needed a space to discuss and explore ideas with peers.…”
Section: Bapp (Arts) Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially in 2009 Durrant and Akinleye redeveloped the first module for the undergraduate cohort of BAPP (Arts). Subsequent changes they made to the curriculum embraced the connectivity of social media (Middlesex University, 2009;Bryant et al, 2013). This new curriculum design aimed at acknowledging that work-based students were less physically present on campus but still needed a space to discuss and explore ideas with peers.…”
Section: Bapp (Arts) Backgroundmentioning
confidence: 99%
“…The team discussions and reflections on student experiences indicated that something that was derived from the professional field itself was also needed. This meant that a "plural representation" of the inquiry process could be introduced to attempt to bridge the gap between physical experiences and verbal descriptions (Akinleye, 2013). A second element of a professional artefact could allow for engagement with communication that is acknowledged within embodied approaches or draw on embodied metaphor (Lakoff and Johnson, 1980) to draw links between the knowledge acquired through the research activity and the on-the-ground professional context in which students could go on to use this knowledge.…”
Section: Heswbl 41mentioning
confidence: 99%
“…Much of the current literature about practice-based studio learning has focused on learning and teaching strategies, and recent higher educational studies use the well-established qualitative case study approach to examine arts-based communities, investigating the nature of faculty-student interactions (Cennamo and Brandt, 2012), developing collaborative support in design studio environments (Vyas et al, 2013) and utilising new technologies to deliver studio learning (Fleischmann, 2014). Collaborative action research projects have facilitated research into developing work-based curriculums to accommodate new members of academic staff in participatory research, which includes students as decision makers who help to share and develop appropriate learning spaces (Bryant et al, 2013). In recent studies, PAR has been used to investigate the issues of diversity and widening participation across creative education and its subsequent impact on students (Hayton et al, 2014).…”
Section: Research Methodologies Methods and Theoretical Frameworkmentioning
confidence: 99%
“…This study considers how the process of and reflection of student-led action research in teacher education can contribute to the professional learning of the teacher educators undertaking the assessment (Auld, Ridgway & Williams, 2013). There is an extensive body of literature on assessment in pre-service teacher education (Auld et al, 2013;Bowen, 2013;Bryant, Akinleye & Durrant, 2013;Fletcher, Meyer, Anderson, Johnston, & Rees, 2012;McDonough, 2006;Medland, 2014;Nolen & Putten, 2007). In this study, we were focusing on reflections based on an action research assessment.…”
Section: Action Researchmentioning
confidence: 99%